Flexible All-Optical Remote Frequency Conversion of 5G Signals to FR1 and FR2 Bands Employing an Optical Comb and Multi-Core Fiber for Next-Generation C-RAN Fronthaul - Vicente Fito; Maria Morant; Roberto Llorente (IEEE Access)
The rapid deployment of 5G wireless networks demands efficient, high performance, dynamically reconfigurable solutions for seamless multi-band frequency conversion and connectivity provision. Efficient centralized radio access networks (C-RAN) can benefit from an all-optical signal conversion and remoting employing optical frequency combs and multicore fiber (MCF) as optical source and transmission media respectively. This paper proposes and evaluates experimentally an all-optical frequency conversion approach based on an optical frequency comb (OFC) generated using a dual-drive Mach-Zehnder modulator (DD-MZM) and transmitted through MCF. The proposed method enables seamless frequency up- and down-conversion across sub-6 GHz and millimeter-wave (mm-wave) bands, leveraging optical heterodyning to achieve low-distortion signal transmission in next-generation C-RAN fronthaul implementations. The performance of the system is evaluated in terms of signal-to-noise ratio (SNR) and error vector magnitude (EVM) of the frequency-converted 5G signals. The results demonstrate that frequency-converted replicas exhibit minimal EVM degradation, with values consistently below 10.5%, ensuring compliance with 3GPP 5G NR standards. Additionally, we analyze how the modulation order affects the 5G performance, finding that lower-order orthogonal frequency division multiplexing (OFDM) schemes (e.g., QPSK) maintain robust performance at lower SNRs, while higher-order OFDM schemes (e.g., 64QAM and 256QAM) require higher SNRs for satisfactory performance meeting 3GPP threshold recommendations. Furthermore, we explore the role of multiple modulated optical carriers over the MCF media, showing that increasing the number of modulated carriers improves SNR and reduces the fluctuation of the received EVM. The EVM fluctuation is measured for different configurations, using one or two modulated optical carriers. The maximum access network reach is calculated by measuring the power margin available using the same receiver. Considering the propagation losses and expected crosstalk-induced SNR penalty of a 7-core MCF, a 23.6 km extension could be reached when using two modulated carriers for optical heterodyning compared with a single modulated carrier without frequency conversion. Finally, the impact of power balance of the optical carriers used for optical heterodyning is also evaluated in terms of EVM and SNR of the original and upconverted signals. These findings highlight the potential of MCF networks using an OFC for the transmission of 5G signals as a scalable solution for next-generation C-RAN supporting agile reconfiguration in multiple frequency bands.